Multiple Roles of Working Academic Women and their Relationship with Family Problems in Yemeni Universities: A Field Study at Aden University - Abdulqawi, Saif Mohsen (Journal of Humanities & Social Sciences, 2025)
The study aimed at identifying the reality of multiple roles of a working woman and their relationship with the family problems in the Yemeni universities: A field case study on (63) of female academics working at the faculties of the University of Aden. To achieve the objectives of this study, the researcher used the descriptive analytical approach and the questionnaire to collect the data of the field study. After analyzing and discussing the data, the study revealed a number of findings such as that the main reason of a working woman is to depend on herself and achieve self-sufficiency, and the husband's consent for his wife's working is mainly attributed to economic conditions. In general, these women's children do not experience any decline in their academic performance. A working woman is capable of fulfilling various roles, whether at work or within the family, and her work does not pose any problems for her, as she is capable of managing both her occupational and  familial duties. The findings also revealed that the most prominent difficulty encountered by the working woman is insufficiency of her monthly income because of rising prices and deteriorating living conditions. Security is achieved through her work, her husband's work, or by working together to provide a happy life, and by the man's understanding of the working woman. The study concludes with a number of Recommendations, such as: creating a work environment for women, exchanging family roles with men, and solving problems wisely.
Keywords: role; family; woman's roles; family problems; working woman